EXCESSIVE USE OF MOBILE PHONES AND ITS PSYCHOLOGICAL IMPACT ON NURSING STUDENTS - CHANDIO , K; MEMON , PA; CHANNAR , HB; NOHRI , MUH; BHACHO , AH; DEAN, R (Biological and Clinical Sciences Research Journal, 2023)
As we advance into the digital era, mobile devices have become integral to our daily interactions. Nevertheless, an intensified engagement with these devices has prompted concerns about potential psychological implications among nursing students, influencing their scholastic achievements and personal wellness. The primary objectives of this study were to gauge the frequency and modalities of mobile phone utilization among nursing students, ascertain its effects on their sleep quality, and evaluate its interference with academic and work-related tasks. The study additionally aimed to discern the students' perceived dependency on mobile phones and its subsequent impact on interpersonal relationships. This study employed a descriptive cross-sectional methodology, focusing on the student population at People's Nursing School, LUMHS Jamshoro. A cohort of 162 students was enlisted through a non-probability convenience sampling technique. A meticulously crafted questionnaire served as the primary tool for data collection, capturing an array of participant experiences and viewpoints. A predominant segment of the participants comprised females from middle-income families, boasting an average age of 20.83 (Std. Dev = 1.34). A substantial proportion (58.6%) reported smartphone engagement of less than 6 hours daily. Elevated anxiety levels were observed, with a notable fraction attributing their stress to mobile phone usage. Approximately 32.7% posited that their sleep quality was compromised due to their phone habits. Moreover, 35.8% indicated strained relationships with friends and family due to increased mobile engagement. Several participants emphasized key concerns such as insomnia and profound feelings of isolation linked to heightened mobile usage. The data highlights an urgent need to address the multifaceted psychological and social ramifications of unrestrained mobile phone interactions among nursing students. While these devices usher in many conveniences, their unchecked usage could catalyze profound challenges, emphasizing the need for strategic interventions to safeguard prospective healthcare professionals' mental and emotional health.